The adipokine preadipocyte factor-1 is downregulated in preeclampsia and expressed in placenta. Issue 2 (October 2015) - Schrey, Susanne; Wurst, Ulrike; Ebert, Thomas; Kralisch, Susan; Drewlo, Sascha; Stepan, Holger; Lössner, Ulrike; Platz, Martin; Kratzsch, Jürgen; Stumvoll, Michael; Fasshauer, Mathias
Highlights Circulating Pref-1 levels are significantly lower in preeclampsia patients. Serum Pref-1 significantly decreases postpartum as compared to antepartum levels. Significant Pref-1 protein synthesis is detected in placental tissue.